An experimental study on the steel corrosion behavior in NaCl-immersed concrete under hydraulic pressure. (22nd August 2022) - Park, Jae-Chan; Jung, Hyung-Jo
Highlights: Steel corrosion in concrete under immersion and hydraulic pressure is studied. Experiments were performed in a hydraulic-pressure environment based on ASTM G109. Rebars initially corroded significantly in NaCl under hydraulic pressure. Corrosion rate is high because of rapid penetration of water and NaCl in concrete. Corrosion rate decreases after reaching maximum value under high hydraulic pressure. Abstract: Steel corrosion in reinforced concrete structures occurs by depassivation from chloride-ion diffusion. The corrosive products expand, causing cracking and structural deterioration. This study aims to determine steel corrosion tendencies in concrete when immersed in NaCl under hydraulic pressure. Experiments were performed in a hydraulic-pressure environment based on ASTM G109. The results show that rebars initially corroded significantly in NaCl-immersed environment under hydraulic pressure. Rebars corroded faster in high-hydraulic-pressure environment, with high corrosion rate because of rapid water and NaCl penetration into concrete. However, the corrosion rate decreased drastically after reaching maximum value under high hydraulic pressure because of corrosion products and oxygen reduction in pores from rapid moisture penetration. These results are expected to be useful for safety maintenance and management of civil structures exposed to deep-sea environments under hydraulic pressure.